TO IMPROVE UNDERWATER CONTROL OF TANKS (Academicia Globe: Inderscience Research, 2022)
This article is devoted to an innovative approach to improving the T-62 tank's ability to overcome obstacles under water. In order to expand the capabilities of the T-62 tank under water, a 3D model was developed and used, and information was given about the results of laboratory tests of the innovative system installed in the tank through this model.